Foreign exchange risk exposure, hedging behaviour, and corporate valuations: Evidence from South Africa - Molele, Mashukudu Hartley (Graduate School of Business (GSB), 2018)
The international business and finance literature documents a so-called exchange rate exposure puzzle. The exchange rate exposure puzzle refers to the apparent lack of empirical support for theories posited in the finance literature which predict that in the advent of an increasingly globalising world economy, nonfinancial firms should report high levels of foreign exchange risk exposure. The majority of the studies are based on the developed market context and the emerging markets of the ASEAN region. However, there is scant literature in the context of the emerging markets of the African continent. Considering that the estimation of foreign exchange risk exposure is based on the application of asset pricing models, and the fact that emerging markets are generally found to be partially segmented, the so-called exchange rate exposure puzzle cannot be generalised to the emerging markets of Africa. The general aim of the study was to examine the level of foreign exchange exposure of nonfinancial firms in South Africa, hedging behaviour and their effect on corporate value, taking into account idiosyncratic factors. Foreign exchange risk exposure were estimated at more than 40% for all for proxy currencies on the basis of the standard augmented market model. However, after controlling for idiosyncratic factors exposure levels were found to range between 6.5% and 12%. These results indicate the importance of controlling for the effects of idiosyncratic factors in the estimation of foreign exchange risk exposure in the context of emerging markets. Furthermore, the study found exposure levels to be time-varying with respect to the trade-weighted exchange rate. An indirect test of asymmetric exposure revealed results that are similar to those estimated on the basis of a more direct test in the form of a Nonlinear ARDL model and these were found to be higher than those estimated on the basis of the standard model. iii The study established that South African nonfinancial firms are likely to hedge using foreign currency derivatives when they have foreign sales, have lower interest coverage, have access to capital markets, are highly liquid, have higher gearing, and whose management have equity stakes in the firm. In contrast, South African nonfinancial firms were found to be more likely to hedge using foreign currency denominated debt when they are small in size, have foreign sales, are highly leveraged, have less growth opportunities, are highly liquidy. The magnitude of the marginal effects show that foreign sales is the single most important determinant of the decision to hedge using foreign currency denominated debt. In contrast, managerial incentives play no role in the decision to hedge using foreign currency denominated debt. Corporate currency risk management using foreign currency derivatives and foreign currency denominated debt was found to have no beneficial effects on corporate value. However, foreign currency denominated debt use was found to be much more effective than the use of foreign currency derivatives. The study identified the need for South African firms to adopt a more strategic approach in the management of economic foreign exchange risk exposure.